Pneumatologi kepemimpinan: Rekonstruksi teologis servant leadership dalam formasi mahasiswa teologi di era post-secular - Robinhot Sihombing; Tetti Manullang; Ruslan J. Pardosi; Justice Zeni Zari Panggabean; Surnika R. Manik (KURIOS, 2025)
The leadership crisis in Indonesian theological higher education reveals a fundamental tension between the transactional-managerial leadership model and the theological imperative of Christocentric character formation. This article constructs a pneumatological framework of servant leadership that goes beyond the behavioral-instrumental approach to the ontological formation of theology students. Through biblical hermene-utics (Mrk 10:41-45; Jn. 13:1-17; Phil. 2:5-11) and a phenomenological analysis of the formative experiences of students at the Institut Agama Kristen Negeri Tarutung, this study identifies three constitutive dimensions: Christological kenosis as a paradigm of decentering the ego, pneumatological empowerment within the formative community, and ecclesial praxis as a laboratory for altruistic leadership. The findings demonstrate that the integration of liturgy, relational mentoring, and community immersion results in a transformation of leadership identity from technical competence to a habitus of service. This article contributes to the practical theology of Christian higher education by offering a formative model that synthesizes biblical orthodoxy, spiritual tradition, and transformative pedagogy.   Abstrak Krisis kepemimpinan dalam pendidikan tinggi teologi Indonesia mengungkapkan ketegangan fundamental antara model kepemimpinan transaksional-manajerial dengan imperatif teologis pembentukan karakter kristosentris. Artikel ini mengonstruksi kerangka pneumatologis servant leadership yang melampaui pendekatan behavioral-instrumental menuju formasi ontologis mahasiswa teologi. Melalui hermeneutika biblis (Mrk. 10:41-45; Yoh. 13:1-17; Fil. 2:5-11) dan analisis fenomenologis terhadap pengalaman formatif mahasiswa Institut Agama Kristen Negeri Tarutung, penelitian ini mengidentifikasi tiga dimensi konstitutif, seperti kenosis kristologis sebagai paradigma ego-decentering, pemberdayaan pneumatologis dalam komunitas formatif, dan praksis eklesial sebagai laboratorium kepemimpinan altruistis. Temuan menunjukkan bahwa integrasi liturgi, mentoring relasional, dan imersi komunitas menghasilkan transformasi identitas kepemimpinan yang melampaui kompetensi teknis menuju habitus melayani. Artikel ini berkontribusi pada teologi praktis pendidikan tinggi Kristen dengan menawarkan model formatif yang menyintesis ortodoksi biblis, tradisi spiritual, dan pedagogi transformatif